2014
DOI: 10.1167/iovs.14-14109
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Trichostatin A and Vorinostat Inhibit TGFβ2-Induced Lens Epithelial-to-Mesenchymal Cell Transition

Abstract: Histone deacetylase inhibitors, TSA, and SAHA prevent EMT in lens epithelial explants. The results also suggest that the epigenetic modifiers are the potential targets to control PCO after cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 51 publications
0
28
2
Order By: Relevance
“…The use of explant cultures has also been applied to the porcine and human lens Xie et al, 2014). These systems have recently been used to demonstrate that histone deacetylase inhibitors can suppress TGFb induced aSMA expression, thus suggesting that epigenetic modifiers could play a role in treating PCO (Xie et al, 2014).…”
Section: Explant Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of explant cultures has also been applied to the porcine and human lens Xie et al, 2014). These systems have recently been used to demonstrate that histone deacetylase inhibitors can suppress TGFb induced aSMA expression, thus suggesting that epigenetic modifiers could play a role in treating PCO (Xie et al, 2014).…”
Section: Explant Culturesmentioning
confidence: 99%
“…These systems have recently been used to demonstrate that histone deacetylase inhibitors can suppress TGFb induced aSMA expression, thus suggesting that epigenetic modifiers could play a role in treating PCO (Xie et al, 2014). In addition, human lens explants have been employed to understand the possible roles of growth factors, such as HGF and EGF in PCO, through detection of receptors and investigation of signalling pathways (Maidment et al, 2004;Wormstone et al, 2000).…”
Section: Explant Culturesmentioning
confidence: 99%
“…In addition, aberration in integrin‐mediated cell anchoring has also been implicated in lens epithelial cell EMT (Mamuya et al ., 2014). Recent studies have also shown a role for aldose reductase, MMP, microRNA, and histone deacetylases in lens epithelial cell EMT (Yadav et al ., 2009; Wang et al ., 2013; Korol et al ., 2014; Xie et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…TSA is another pan-HDACI similar to SAHA that inhibits HDACs 1, 2, 3, 4, 6, 7, and 10 and showed potent anti-cancer effects in pre-clinical experiments [8, 2527]. There are pre-clinical studies reporting encouraging results for both SAHA and TSA in the treatment of glioblastomas [18, 19, 2831]. However, clinical trials showed that the effect was modest, and it is recommended to use HDACIs with other cytotoxic drugs for treating glioblastomas [32, 33].…”
Section: Discussionmentioning
confidence: 99%